A SOCIOLOGICAL POST-MORTEM OF ISSUES IN THE AROGBO IJAW-ILAJE CONFLICT: AN AGENDA FOR PEACE - Ayoyo, Damilohun Damson (European Scientific Journal, ESJ, 2015)
Given the persistence, re-enactment and escalation of many ethnic conflicts in Africa, this study examined issues in the 1998/1999 Arogbo Ijaw-Ilaje conflict in Nigeria. This was done against the background that African leaders and mediating agencies often lack political will and commitment to resolve issues in ethnically-rooted conflicts. Using in-depth interviews and multi-stage sampling technique, 45 stakeholders from Arogbo-Ijaw and Ilaje were involved in the study. Findings revealed the Arogbo Ijaw-Ilaje conflict was centered on non-resolution of land and boundary dispute, struggle for resource control, fear of domination, marginalization, religious leadership crisis and quest for political autonomy arising from conflicts between the two groups in the past. Findings further revealed understanding ethnic conflicts goes beyond immediate factors to involve unresolved historical issues between groups concerned. The study concluded that non-resolution of issues in ethnic conflicts can undermine sustainable peace and provide ‘soft-spots’ for future re-enactment. The study recommended the need for peace builders, mediators, negotiators and parties to the conflict to direct peace efforts towards effective resolution of issues in the conflict as failure to do so would mean another evil day between the two ethnic groups may be ahead.